Establecimiento de una red Geodésica en Tegucigalpa (Honduras) mediante tecnologías GPS - Bosque Sendra, Joaquín; Malpica Valesco, José Antonio; Maza Vázquez, Francisco; Rodríguez Díaz, Guadalupe; Pina de Caríaz, Ma Cristina; MC Castellanos, Yeny; González, Mauricio; Pavón, Jimy; Plata Rocha, Wenceslao; Andrés Meza, Oscar; Carias Arias, Antonio B; Soriano Sanz, Maria Luisa; et al. (Ciencias Espaciales, 2015)
DOI: http://dx.doi.org/10.5377/ce.v3i2.1930